Elder abuse with multimorbidity and its relationship with quality of life - Giraldo Rodríguez, Liliana; Pavón León, Patricia (Horizonte Sanitario, 2023)
Objective: To estimate the prevalence of elder abuse and multimorbidity, as well as to analyze if elder abuse in the presence of multimorbidity is associated with self-perceived health-related quality of life in older adults from Xalapa, Veracruz. Material and methods: Material and methods: This is a cross-sectional study based on data collected in a representative survey of older people (≥60 years) from Xalapa, Veracruz. The survey was conducted from September 2018 to January 2019 (n = 993). A questionnaire was used to collect demographic, socioeconomic, and health data. Elder abuse was assessed using the Geriatric Mistreatment Scale (GMS-22 items) and health-related quality of life using the short form 36 health survey questionnaire (SF-36). Descriptive analyzes were performed to estimate the prevalence and logistic regression models to analyze the association. Results: The prevalence of elder abuse was 16.2%. The types of elder abuse were psychological (13.6%), economic (4.8%), physical (3.2%), neglect (2.3%) and sexual abuse (0.5%). The prevalence of multimorbidity was 43.2%. Older people with both elder abuse and multimorbidity presented lower health-related quality of life in the dimensions of physical role (OR 2,362 IC: 1,254-4,452), body pain (OR 2,278 IC: 1,277-4,065) and mental health (OR 2,94 IC: 1,499-5,766). Conclusions: Elder abuse and multimorbidity are common problems in the older population in Xalapa, Veracruz, Mexico; the presence of these two events is associated with lower health-related quality of life. Future research should focus on improving understanding of the family relationships of older people with multimorbidity, and health care and social services should take these findings into account to address the elder abuse with multimorbidity before further adverse situations occur that impact their health-related quality of life.